A Strategy for the Simultaneous Synthesis of Methallyl Alcohol and Diethyl Acetal with Sn‐β. Issue 23 (4th December 2017) - Hu, Wenda; Wan, Yan; Zhu, Lili; Cheng, Xiaojie; Wan, Shaolong; Lin, Jingdong; Wang, Yong
Abstract: Invited for this month′s cover is the group of Yong Wang at Xiamen University. The cover picture shows a strategy to simultaneously produce two important chemicals, namely, methallyl alcohol and diethyl acetal from methacrolein in ethanol solvent at low temperature on Beta zeolites modified by tin (Sn‐β catalysts). The Full Paper itself is available at10.1002/cssc.201701435 . Abstract : "The biggest challenge was to understand the complex reaction network and the reaction mechanism…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201701435 . View the Front Cover here:10.1002/cssc.201702213 .